Surface recombination and charged exciton in nanocrystal quantum dots on photonic crystals under two-photon excitation - Xu, Xingsheng (Nature Publishing Group, 2014)
In this study, the two-photon excited fluorescence spectra from cadmium selenide quantum dots (QDs) on a silicon nitride photonic crystal (PhC) membrane under femtosecond laser irradiation were investigated. These spectra can be fit to a tri-Gaussian function in which one component is negative in amplitude, and in which the Gaussian components with positive amplitude are assigned to exciton emission and charged-exciton emission and that with negative amplitude is assigned to absorption from surface recombination. The photonic crystal enhance the charged-exciton emission and exciton emission and, at the same time, also the absorption from surface recombination. Both the charged-exciton emission and the surface recombination are related to Auger recombination; therefore, the photonic crystal controls both radiative recombination and non-radiative recombination. The asymmetries of the two-photon excited fluorescence spectra are due to not only the location of the resonant guide mode of the PhC slab but also the enhancement of the absorption from surface recombination by PhC.